Pengaruh Job Insecurity dan Stres Kerja Terhadap Turnover Intention Pada Driver Gojek - Glorian Stevani Hallo; Yustina Erti Pravitasmara Dewi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
Turnover intention is a subjective perception of employees to quit their current job with the aim of looking for other opportunities. Turnover intention must be considered so that it does not happen to the company. Factors that cause turnover intention to occur are job insecurity and work stress which are still not paid attention to by the company. This study aims to partially examine the effect of job insecurity and job stress on turnover intention of Gojek drivers in Salatiga. This research was conducted on 40 Gojek drivers. Data collection was carried out by distributing questionnaires directly to Gojek drivers in Salatiga. The results of the study found that job insecurity had no effect on turnover intention but job stress had a significant effect on turnover intention. This is because the job insecurity experienced by the driver can be controlled properly so that it helps the driver in dealing with work stress and can minimize turnover intention.